The effect of intrinsic motivation, extrinsic motivation and work environment on academicians’ job performance at public universities in Malaysia - Saraniya, Kataraian (2024)
The performance of academicians at public institutions is essential for institutional growth, impacting not only teaching quality but also research productivity, student engagement, and overall academic reputation. The main objective of this research is to study the effect of intrinsic motivation, extrinsic motivation and work environment on academicians’ job performance at public universities in Malaysia. The inconsistency of findings in past literature between the independent variable has prompted researchers to explain the inconsistency. The survey questionnaire was distributed online to academic staff of northern region public universities. Herzberg's Two-Factor Theory underpins the proposed theoretical framework. Herzberg's Two-Factor Theory states that employee motivation is driven by two elements: motivators (intrinsic variables such as success, recognition, and growth) and hygiene factors (extrinsic factors such as salary, work environment, and corporate laws). The model was tested utilizing Partial Least Squares Structural Equation Modelling (PLS-SEM) using data that was collected from 212 academicians from northern region public universities. The results show that intrinsic and extrinsic motivation has a significant relationship with academicians’ job performance, while work environment is found to be insignificant in academicians’ job performance. This study contributes to public universities building comprehensive motivating methods that meet intrinsic and extrinsic demands and optimise the work environment to improve job satisfaction and productivity among academicians.